The Efficacy and Safety Of Using Hydrochlorothiazide As Adjuvant Therapy In Pediatric Urinary Tract Infections - Jameel, Watheq I. (AL-Kindy College Medical Journal, 2018)
Background: Acute urinary tract infection is a common bacterial infection causing illness in infants and children. At age of seven, 8% of girls and 2% of boys will have at least one episode. Although drinking water and using home remedies are known to help to flush away bacteria and keeps them from sticking to the bladder wall, researches to test the efficacy and safety of hydrochlorothiazide's diuretic effect as adjuvant to the antibiotics in pediatric age groups are lacking, and so this research was to address this subject.Objectives: To assess the effectiveness   and  the safety of hydrochlorothiazide as adjuvant therapy to the antibiotics in treating acute urinary tract infection in pediatric age group.Type of the study: Case-control prospective study.Methods: The study was done including eight hundred sixty five patients ((In_ & Out_ patients)): The patients included were aged from few hours (neonates) to 16 years old, Those who attended three pediatric hospitals- department of nephrology of:The Central Child Teaching Hospital,Al- Elwyia Pediatric Hospital andIbn Al-Baladi HospitalResults: 215 patients in group 1 ((97.3%)) presented with cystitis and 6 patients ((2.7%)) with pyelonephritis, And In group 2, 243 ((96.4%)) with cystitis and 9 patients ((3.6%)) with pyelonephritis.The urine cultures were negative in ((76.4, 80.1, 85.9,95.0  percentages of patients)) after ((10 days, 1 month, 3 months and 6 months respectively)) in group1 vs. ((60.3, 68.60,75.8,85.3 )) after the same periods in group 2 ((p-value=0.04 at 10 days, 0.03 at 1month, 0.04 at 3 month and 0.02 at 6month)).Conclusions: This research had concluded that 5 days of treatment with antibiotics and hydrochlorothiazide were effective and safe to treat children with urinary tract infection. Hydrochlorothiazide (as a diuretic and hypocalciuric agent) adjuvant to the antibiotics in pediatrics was safe and effective to: Decrease duration of treatment and hospitalization days, Improve clinical responses to antibiotics and Decrease risk of complications of UTI.